Application of surf-riding and broaching criteria for the systematic series D models. (15th December 2018) - Begovic, E.; Bertorello, C.; Boccadamo, G.; Rinauro, B.
Abstract: The Second Generation Intact Stability Criteria (SGISC) have been introduced after the occurrence of stability-related accidents, which clearly demonstrated that "actual" intact stability criteria were not adequate. New generation criteria are based on the physical and failure mode analysis of parametric roll, pure loss of stability, surf-riding/broaching, dead ship condition and excessive accelerations. This paper is focused on the verification of surf-riding/broaching vulnerability criterion of semi-displacement hull form of the Systematic Series D by Kracht and Jacobsen (1992) representative of several naval ships built during 90ties. Levels 1 and 2, as amended in IMO relevant documents, have been calculated for all seven D Systematic Series ships from resistance and propulsion performances measured in calm water. After several and counteracting changes in the wave celerity definition by IMO, the calculations have been performed for all models with both linear and non-linear formulation. The influence of the diffraction component on the wave surging force has been analyzed according to the works of Feng et al. (2015, 2017). The total surge force, calculated by 3D panel method, has been compared against actual IMO formulation and calculation of vulnerability has been performed for three hulls. The limit Froude number for the considered 90 m ships is increased by improving the accuracy of 2nd level calculation, taking into account only nonlinear wave celerity or diffraction component and linear wave celerity. Highlights: Surf-riding/broaching vulnerability criteria within Second Generation Intact Criteria frame has been studied. Calculations have been performed for the semi-displacement hull forms of the Systematic Series D. Effect of wave celerity definition i.e. linear/non-linear on the surf riding vulnerability has been investigated. Influence of the diffraction component on the wave surging force, calculated by 3D panel method, is analyzed for 3 models. Surf-riding occurrence boundary with and without diffraction effect is assessed for hull D1.